1999
DOI: 10.1046/j.1525-1373.1999.d01-43.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tea Consumption on Oxidative Stress in Smokers and Nonsmokers

Abstract: While the anticarcinogenic effects of tea in animal models have been reported by several groups, human epidemiological studies examining tea consumption and cancer prevention have produced equivocal results. The beneficial properties of tea to human health may be related to the antioxidant properties of tea components. However, little evidence has been provided that tea consumption can either increase the antioxidant capacity or decrease oxidative stress in humans. In the present study, the effects of tea trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 18 publications
1
27
1
Order By: Relevance
“…This may partly explain why many studies have given contradictory results. For example, whereas there appears to be no effect of consumption of catechin-rich green or black tea on the oxidation of LDL of smokers ex vivo (Princen et al 1998;Cherubini et al 1999), a process potentially associated with the development of the atheromatous plaque, other trials indicate that tea consumption by smokers and non-smokers is associated with a decrease in markers of oxidative DNA damage as estimated by 8-hydrox-deoxyguanosine in leucocytes and urine (Klaunig et al 1999). Urinary and plasma malonaldehyde concentrations, which are crude measures of lipid peroxidation, were also decreased in smokers (Klaunig et al 1999) and healthy females (Freese et al 1999) following consumption of catechin-rich beverages or extracts.…”
Section: Antioxidant Actionmentioning
confidence: 99%
“…This may partly explain why many studies have given contradictory results. For example, whereas there appears to be no effect of consumption of catechin-rich green or black tea on the oxidation of LDL of smokers ex vivo (Princen et al 1998;Cherubini et al 1999), a process potentially associated with the development of the atheromatous plaque, other trials indicate that tea consumption by smokers and non-smokers is associated with a decrease in markers of oxidative DNA damage as estimated by 8-hydrox-deoxyguanosine in leucocytes and urine (Klaunig et al 1999). Urinary and plasma malonaldehyde concentrations, which are crude measures of lipid peroxidation, were also decreased in smokers (Klaunig et al 1999) and healthy females (Freese et al 1999) following consumption of catechin-rich beverages or extracts.…”
Section: Antioxidant Actionmentioning
confidence: 99%
“…This benefits of green tea are attributed to its high content of antioxidants and anti-inflammatory catechins. 15,19,21 Nonetheless, this data may not reflect the effects of a single dose of green tea administration neither in BP nor in antioxidant activity in response to a session of physical exercise. Belza et al 22 found that a single dose of green tea (500 mg) did not cause significant effects on the blood pressure response of young adults.…”
Section: Discussionmentioning
confidence: 81%
“…It was beyond the scope of this review to include and examine sources from 'grey' literature. Despite the variability of effect, with some studies finding conflicting outcomes [28][29][30], the majority of the current literature appears to support the positive therapeutic effect derived from GT consumption [1,[9][10][11][12][13][14][15][31][32][33][34]. Furthermore, as tea consumption is high globally, it could be proposed that even modest health effects in humans may have major beneficial implications for global population health and reduction in CVD risk [21,35].…”
Section: Methodsmentioning
confidence: 99%